PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) BERBANTUAN MEDIA AUDIOVISUAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SEKOLAH DASAR - Esther Evi Rianty Siburian; Silalahi, Eka Kartika; Simarmata, Ester Julinda; Tarigan, Paska Sriulina; HS, Dyan Wulan Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low mathematics learning outcomes of elementary school students, which are often associated with conventional instruction and the limited use of engaging learning media. This study aimed to examine the effect of the Numbered Heads Together (NHT) cooperative learning model assisted by audiovisual media on fourth-grade students’ mathematics learning outcomes. A quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design was employed. The sample consisted of 48 students, including 28 students in the experimental class and 20 students in the control class. The experimental class was taught using the NHT cooperative learning model assisted by audiovisual media, while the control class received conventional instruction. The research instrument was a mathematics achievement test administered as a pre-test and post-test. The data were analyzed using the Lilliefors normality test, Levene’s homogeneity test, and an Independent Sample t-test. The results showed that the mean post-test score of the experimental class was 87.29, which was higher than that of the control class at 79.40. The t-test result indicated that tcount > ttable, namely 2.840 > 2.010 at the 0.05 significance level. Therefore, the NHT cooperative learning model assisted by audiovisual media had a significant effect on students’ mathematics learning outcomes. This model promoted active participation, individual accountability, group collaboration, and helped students understand mathematical concepts more concretely.